Does entrepreneurship improve the livelihood of young people? Evidence from the NDE program beneficiaries in Kano state, Nigeria - Adeyanju, Dolapo; Akomolafe, Kehinde J.; Mburu, John I.; Ohanwusi, Evelyn O.; Adebayo, Solomon A.; Joy, Chiagoziem (Informa UK Limited, 2023)
Entrepreneurship has evolved into a valuable tool for facilitating job creation in response to Nigeria’s youth bulge and declining job opportunities in the formal sector. This study assessed the impact of entrepreneurship on youths’ livelihood, focusing on the National Directorate of Employment (NDE) program in Kano state. The study employed both qualitative and quantitative methods. A total of 266 respondents, including 148 young entrepreneurs and 118 non-entrepreneurs, were sampled using a multi-stage sampling technique, with Focused Group Discussions (FGDs) used to collect qualitative data from 25 youths. Data were analyzed using descriptive statistics and an Endogenous Switching Treatment Effect Regression (ESTER) model. The descriptive analysis showed that engagement in entrepreneurship was determined by age, having consistent income source, credit access, number of entrepreneurs in the household, access to entrepreneurship training, household size, and asset ownership. Even though entrepreneurs earned higher monthly income than non-entrepreneurs, their income was just slightly above the Nigerian minimum wage. Furthermore, asset ownership, access to credit, group membership, and access to training, all of which are strong predictors of entrepreneurship, were higher among entrepreneurs compared to non-entrepreneurs. The findings also revealed that entrepreneurs had better livelihood outcomes, as measured by income and self-assessed living condition, than non-entrepreneurs. Even though these outcomes could have resulted from other externalities, the empirical analysis helped to address such endogeneity, thereby attributing the outcome estimates solely to entrepreneurship. These results, therefore, show the relevance of entrepreneurship in alleviating poverty and generating better livelihood outcomes for young Nigerians.